Analisis Cara Belajar Siswa Berprestasi pada Muatan Matematika Kelas III di SD Negeri 10 Langkai - Azizah, Rana; Nyoto; Mardiana, Dina (Pusat Kajian Bahasa Daerah & Budaya, 2024)
The way students learn is one of the important factors that greatly influences the achievement or learning outcomes studied. In education, it is often known that each student has a different way of learning. A good way of studying will determine success in learning. This research aims to find out how outstanding students in class III learn at SD Negeri 10 Langkai. This research uses qualitative research. Data collection uses observation methods, interview methods, and documentation methods. This research took 3 student subjects who had achievements in Class III of SD Negeri 10 Langkai. Meanwhile, the data analysis uses descriptive of Mile and Huberman’s analysis which consists of: data reduction, data presentation and drawing conclusions. The results of the research found that the learning methods for high-achieving students are: (1) making a study schedule during the day or in the evening to prepare for the next day's learning, (2) reading textbooks when the learning process has begun with the teacher's direction to know the material to be read, (3) record the material, in its application in class III of SD Negeri 10 Langkai there are rules for recording the material. Students are not allowed to make mistakes when the teacher is explaining, (4) repeating material, not all students repeat material that has been taught at school, but quite a few students also repeat material at home so that the material they get sticks in students' minds (5) do the tasks given by the teacher very well which will determine the learning outcomes. Students who excel have different ways of learning from other students. Students who excel will be more consistent in carrying out the learning methods they have created, so that the learning results they get will be more satisfying.